STUDENTS’ DIFFICULTIES IN SOLVING SYNTHESIS ORGANIC COMPOUND PROBLEMS - Amsad, Lusia Narsia; S, Liliasari; Kadarohman, Asep; Sardjono, Ratnaningsih Eko (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
Solving the synthesis problem of organic compounds requires the understanding of certain organic chemical concepts. Students need to integrate organic chemical concepts to analyze the synthesis stage of organic compounds. Therefore, purposed of this research is want to find the difficulties possessed by students in solving organic synthesis problem. The participants of this research are 14 students of chemistry education in one state university in Papua, Indonesia. The type of this research is descriptive research. The research using multiple choices with reasoning test and essay test as the instruments, that consist of 6 items of multiple choices and 3 essay items. The results analyze by percentage and described. In this research, students are given issues concerning to the concepts of organic chemistry and the synthesis of organic compounds. The result shows students' understanding on the concept of functional group of organic compound is 79%, organic compound structure is 57%, organic stability is 22%, electrophile and nucleophile is 36%, while the concept of reagent, required condition and related product stereochemistry of organic compound less than 20%. It shows students having more difficulties in the concepts of reagent, required condition and related product stereochemistry of organic compound.